The representation of female characters in Butler’s translation of the “Odyssey”: a corpus-based approach (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
In The Authoress of the Odyssey (1897), Samuel Butler developed a notably controversial intuition about the poem’s author. In his analyses, he concluded that the same person could not have created the Iliad and the Odyssey: whilst the former was undoubtedly written by the Greek male poet Homer, the latter should be regarded as a companion piece to the Iliad and was instead the work of a «young, headstrong, and unmarried» woman (as the title to his chapter VII phrases it) from Magna Graecia, more precisely Trapani, Sicily. This theory rested upon his assumption that female characters in the Odyssey are favourably portrayed, whereas there is a relative disregard for male characters (Ebbott 2005). Butler’s prose translations of the Iliad and the Odyssey became highly successful and are still consulted nowadays; however, his views on the authorship of Homer’s works were severely criticised back then. The purpose of this paper is to explore to what extent Butler’s theory impacted his translation of the Odyssey by analysing his portrayal of female characters through collocations («word sketches»); to this end, an approach combining corpus linguistics (Fischer-Starcke 2010), corpus stylistics (Mahlberg 2012), and translational sty-listics (Boase-Beier 2006) will be adopted as the research design for this study. This study analyses the target text to understand how gender is represented and received (Venuti 2019) through linguistic choices.
Keywords: Odyssey; Butler; corpus stylistics; translation; gender representation